From virtual to reality: the impact of online classes on physical education teaching and learning - Garcia, Francis Edward; Tagare, Ruben Lagunero; Java, Vinus P; Orfrecio, Marlene E; Martinez, Norge D (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: The return to face-to-face physical education (PE) classes after prolonged online learning during the COVID-19 pandemic has exposed significant issues, including reduced physical competence, student disengagement, and weakened social interaction. While many studies have focused on instructional strategies during online learning, limited research has explored how students' attitudes and motivation affect their re-engagement in PE during the post-pandemic transition. Research Objectives: This study aims to examine the influence of student attitudes and motivation on their success in physical education amid the shift back to in-person learning. Methods: A qualitative approach was employed involving 10 students and 6 PE instructors from higher education institutions, selected through purposive sampling. Data was gathered via in-depth interviews and analysed using Colaizzi’s phenomenological method, with member checking to validate findings. Findings/Results: Students experienced difficulties in skill performance and social reintegration, often accompanied by low confidence and reduced enthusiasm. Teachers highlighted behavioural issues, a lack of participation, and challenges in reestablishing productive classroom dynamics. Conclusion: These findings suggest a need to support students’ psychosocial and physical readiness through motivational and attitudinal interventions. For educators, fostering an engaging learning atmosphere and leveraging blended competencies are key. Future studies should involve broader samples and investigate the long-term effects of this educational transition to inform more effective PE practices.